O uso da modelagem para o ensino da função seno no ensino médio - Santos, Ricardo Ferreira dos (2014)
This research forms part of the studies for the use of Mathematical Modeling as a teaching strategy. In her a modeling activity for teaching the sine function is presented. The research had two main objectives: to analyze the effects of mathematical modeling in high school in order to achieve meaningful learning; and evaluate a proposed approach for modeling, through stages and phases. In this second case it was intended to verify that the protoganismo teacher in presenting the phenomenon preserves the desired features of modeling, increase students' interest in mathematics and motivates you to construct new knowledge. The subjects were fifteen students of the second year of high school to a public school in Sao Paulo, with voluntary participation. This is a qualitative research, developed through participant observation. The model used is shown in Curriculum Proposal of the State of São Paulo. The research is guided by conceptions of modeling Beltrão (2009), Bassanezi (2006) and Ausubel learning theory. The activities were developed using as anchor metric relations in right triangle, the coordinates of points on the Cartesian plane and the study of angles in the trigonometric circle. As a result it can be concluded that modeling can be used in basic education such as teaching methodology, brings results for student participation in the construction of their knowledge, but it is not an easy task because it requires changes in teacher pedagogical practice and student to have to take a participatory attitude. The approach of steps and phases was facilitator